Preyssler Heteropolyacids in the Self‐Etherification of 5‐Hydroxymethylfurfural to 5, 5′‐[Oxybis(methylene)]bis‐2‐furfural Under Mild Reaction Conditions. Issue 17 (2nd August 2017) - Páez, Alexander; Rojas, Hugo A.; Portilla, Omar; Sathicq, Gabriel; Afonso, Carlos A. M.; Romanelli, Gustavo P.; Martínez, José J.
Abstract: The synthesis of 5, 5′‐[oxybis(methylene)]bis‐2‐furfural (OBMF) from 5‐hydroxymethylfurfural (5‐HMF) was studied using bulk and alumina‐supported Preyssler heteropolyacids (HPAs). The formation of OBMF was related to the amount of Brønsted acid sites, and the lowest yield of OBMF was obtained with supported HPAs. However, the Lewis acidity of the HPA supported on Al2 O3 favored the formation of 2, 5‐dimethylfurane. The effects of solvent, catalyst loading, temperature, and reaction time on the selectivity to OBMF from 5‐HMF were studied to optimize OBMF production using bulk Preyssler HPAs; a yield of 84 % to OBMF was obtained at 5 h and 343 K. These results demonstrate that bulk Preyssler HPA is a good candidate for OBMF synthesis under mild reaction conditions. Abstract : Press on with Preyssler : The self‐etherification of 5‐hydroxymethylfurfural (5‐HMF) is studied using Preyssler heteropolyacids (HPAs). The formation of 5, 5′‐[oxybis(methylene)]bis‐2‐furfural (OBMF) is related to the amount of Brønsted acid sites. The Lewis acidity of HPA/Al2 O3 favors the formation of 2, 5‐dimethylfurane. A yield of 84 % of OBMF at 5 h and 343 K is obtained under the optimized conditions.